Analisis Kemampuan Berpikir Kritis Matematis Siswa Berdasarkan Gender pada Materi Teorema Pythagoras di Kelas VIII SMP Negeri 1 Botupingge - R. Pontoh, Nur Lillah; Pauweni, Khardiyawan A. Y.; Takaendengan, Bertu Rianto (Mandalika Mathematics and Educations Journal, 2025)
Critical thinking is a reasoning proces aimed at concluding by first gathering clear data or information. This study aims to analyze the critical thinking skills or male and female students in the Pythagorean Theorem learning material in Class VIII A and Class VIII B at SMP Negeri 1 Botupingge. The study employed a qualitative method with a descriptive research design. The instruments used were tests and interviews. The findings show that in class VIII A, used for validation, empirical testing identified both valid and invalid test items, and the reliability test indicated a very high level of reliability. In class VIII B, where the actual study was conducted, the percentage of male students’ critical thinking skills was 8.33% (high), 75.00% (moderate), and 16.67% (low). Meanwhile, the percentage of famale students was 25.00% (high), 75.00% (moderate), and 0.00% (low).